P48 The 'T2-low' asthma phenotype: could it just be T2-high asthma treated with corticosteroids?. (December 2018) - Jackson, DJ; Aljamil, N; Roxas, C; Fernandes, M; Green, L; Kavanagh, J; D'Ancona, G; Kent, BD
Abstract : Introduction: In recent years patients with asthma have been dichotomised by the degree of their type 2 (T2) airways inflammation into 'T2-high' and 'T2-low' phenotypes. Whilst published reports suggest that 50% of asthma is T2-low, the majority of patients described in these studies are on high dose ICS or OCS. Given that corticosteroids suppress T2 inflammation the true prevalence of T2 low asthma may be lower than reported once steroid doses have been weaned. Method: A retrospective review of asthma referrals to a tertiary asthma clinic was performed. T2 status was recorded on initial assessment and at follow-up using the blood eosinophil (Eos) count and FeNO level. Patients were identified as T2-high if Eos ≥300 cells/mcL or FeNO ≥50 ppb, T2-Low if Eos <300 cells/mcL and FeNO <25 ppb, and T2-Intermediate if Eos <300 cells/mcL and FeNO 25 ppb – 49 ppb. Results: 200 adult patients with a diagnosis of difficult asthma were identified. At initial assessment 71% were T2-High, 18.5% were T2-Low, and 10.5% were T2-Intermediate. Across the two visits 84% were T2-High on at least one visit and 8% were T2-Low on both visits. The mean ICS dose in the T2-Low group was 1740 mcg BDP equivalent/day. 81.3% of T2-Low patients had relevant co-morbidities including dysfunctional breathing (37.5%), obesity (37.5%), gastroesophageal reflux (25%) and VCD (12.5%). Conclusion: Only 8% of severe asthmatics appear persistently T2-Low once their ICS or OCS dose has been optimised. These patients had several co-morbidities that could explain their ongoing symptoms and usage of high levels of treatment. In view of the well-recognised T2-dampening effects of high dose inhaled corticosteroids, the absence of T2 inflammation in these patients may simply reflect overuse of anti-inflammatory treatment in highly symptomatic patients, rather than a true non-T2 inflammatory endotype of asthma.